9 x (x + 5) =729
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
b. 9 × ( x + 5) = 729
x + 5 = 729 : 9
x + 5 = 81
x = 81 - 5
x = 76
![](https://rs.olm.vn/images/avt/0.png?1311)
b. 9 × ( x + 5 ) = 729
x + 5 = 729 : 9
x + 5 = 81
x = 81 – 5
x =76
![](https://rs.olm.vn/images/avt/0.png?1311)
b. 9 × ( x + 5 ) = 729
x + 5 = 729 : 9
x + 5 = 81
x = 81 – 5
x =76
![](https://rs.olm.vn/images/avt/0.png?1311)
= 9 * ( x + 5 ) = 729
= ( 729 : 9 ) - 5 = x
= 81 - 5 = x
= 76 = x
Vậy x = 76
Thử : 9 * ( 76 + 5 ) = 729
= 9 * 81 = 729
Đáp số : 76
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (9458-x)x5=41195 b) (9x x)x6=23490
9458-x =41195:5 9 x x =23490:6
9458-x =8239 9 x x =3916
x=9458-8239 x = 3915:9
x=1219 x=435
c)9x(x+5)=729
x+5=729:9
x+5=81
x=81-5
x=76 k mk nha
a) (9458 - X) x 5 = 41195
9458 - X = 41195 : 5
9458 - X = 8239
X = 9458 - 8239
X = 1219
b) (9 x X) x 6 = 23490
9 x X = 23490 : 6
9 x X = 3915
X = 3915 : 9
X = 435
c) 9 x (X + 5) = 729
X + 5 = 729 : 9
X + 5 = 81
X = 81 - 5
X = 76
![](https://rs.olm.vn/images/avt/0.png?1311)
a, A= 5x415 x 99 - 4x320x 89 = 5x230x318-22x 227x320
=229x318(2x5-32)=229x318
B=5x29x619-7x229x276=5x29x219x3197x229x318
=238x318(5x3-7x2)=228-318
->A:B= 229x318:228:318=2
![](https://rs.olm.vn/images/avt/0.png?1311)
`Answer:`
\(\left(x+\frac{1}{3}\right)+\left(x+\frac{1}{9}\right)+\left(x+\frac{1}{27}\right)+...+\left(x+\frac{1}{729}\right)=\frac{4209}{729}\)
\(\Leftrightarrow\left(x+\frac{1}{3}\right)+\left(x+\frac{1}{3^2}\right)+\left(x+\frac{1}{3^3}\right)+...+\left(x+\frac{1}{3^6}\right)=\frac{4209}{729}\)
\(\Leftrightarrow6x+\left(\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^6}\right)=\frac{4209}{729}\text{(*)}\)
Đặt \(N=\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^6}\)
\(\Leftrightarrow3N=1+\frac{1}{3}+\frac{1}{3^2}+...+\frac{1}{3^5}\)
\(\Leftrightarrow3N-N=\left(1+\frac{1}{3}+\frac{1}{3^2}+..+\frac{1}{3^5}\right)-\left(\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^6}\right)\)
\(\Leftrightarrow2N=1-\frac{1}{3^6}\)
\(\Leftrightarrow2N=\frac{728}{729}\)
\(\Leftrightarrow N=\frac{364}{729}\)
\(\text{(*)}\Leftrightarrow6x+\frac{364}{729}=\frac{4209}{729}\)
\(\Leftrightarrow6x=\frac{3845}{729}\)
\(\Leftrightarrow x=\frac{3845}{4374}\)
`9 xx ( x + 5) = 729`
`x+5=729 : 9`
`x+5=81`
`x=81-5`
`x=76`
Vậy `x=76`
\(9\times\left(x+5\right)=729\)
\(x+5=729:9\)
\(x+5=81\)
\(x=81-5\)
\(x=76\)